Science communication and coproduction: applying the theory of motivated information management to the science-policy interface - Middleton, Lindsey, author; Champ, Joseph, advisor; Anderson, Ashley, committee member; Faw, Meara, committee member (Colorado State University. Libraries, 2020)
Science communication scholarship claims that engagement, dialogue, and interaction are important communicative components. But there are relatively very few studies of dialogic science communication processes from a science communication perspective. This study bridges science communication, interpersonal communication, and science-policy interface research and practice to learn how an interpersonal theory models science-policy communication. When science informs policy and land management, myriad science and policy actors must work together to come to a shared understanding of how science will be used. However, there may be differences across the science-policy interface. How do scientists structure research goals, and how do policymakers and managers set research goals? How do timelines differ? How do communication styles, cultures, and values differ? Can they come to a shared understanding? This work studies the policy side of a particular science-policy interface (coproduction) and describes how science stakeholders, or "information seekers," evaluate the utility of working with information providers from organizations outside their own to inform their own science and policy. Information seekers were interviewed, and they provided insights into their perceptions of (1) the trustworthiness and credibility of information providers, (2) their ability to communicate across the interface, (3) the usefulness of the information provided, and more. Results inform future coproduction practice, but also, this study demonstrates a successful application of an interpersonal communication theory to a science-policy interface. Future work might make further use of the predictive and explanatory utility of this model in science communication with high-priority stakeholders, and interpersonal theories and models arguably stand to further inform the dialogic components of science communication.
Keywords: coproduction; science communication; theory of motivated information management; interpersonal communication; actionable science; science-policy interface